Diagnostic value of combined serum biomarkers for the evaluation of liver fibrosis in chronic hepatitis C infection: A multicenter, noninterventional, observational study - Köksal, İftihar and Yılmaz, Gürdal and Parlak, Mehmet and Demirdal, Tuna and Kınıklı, Sami and Candan, Mehmet and Kaya, Ali and Akhan, Sıla and Aydoğdu, Özcan and Turgut, Hüseyin and et al. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The hepatitis C virus (HCV) infection is important cause of chronic hepatitis. Liver biopsy is considered the gold standard for assessment of fibrosis but this procedure is an invasive procedure. We aimed to evaluate the diagnostic efficiency of non-invasive serum biomarkers, separately and in combinations, on liver fibrosis in treatment-naive chronic hepatitis C (CHC) patients. Materials and Methods: Two hundred and sixteen treatment-naive CHC patients were enrolled from 32 locations across Turkey in this open-labelled, non-interventional prospective observational study. FibroTest®, aspartate aminotransferase-to-platelet ratio index(APRI), aspartate aminotransferase and alanine aminotransferase ratio (AAR), fibrosis index based on four factors (FIB-4), Age-platelet(AP) index and Forns index were measured and compared with Metavir scores got from liver biopsies. Results: Data from 182 patients with baseline liver biopsy were suitable for analysis. One hundred and twenty patients (65.9%) had F0-F1 fibrosis and 62 patients (34.1%) had F2-F4 fibrosis. APRI 0.732 area under the curve(AUC) indicated advanced fibrosis with 69% sensitivity and 77% specificity. FIB-4 0.732 AUC and FibroTest 0.715 AUC indicated advanced fibrosis with 69% and 78.4% sensitivity, and 75% and 71.4% specificity, respectively. The combined use of tests also led to an increase in AUC and specificity. Combinations of FibroTest with APRI and/or FIB-4, and FIB-4 with APRI were optimal for the evaluation of liver fibrosis. Conclusion: Fibrotest, FIB-4, APRI, AP index and Forns index exhibit good diagnostic performance for determining liver fibrosis in CHC patients, and the use of at least two tests together will increase their diagnostic value still further. Cite this article as: Köksal İ, Yılmaz G, Parlak M, et al. Diagnostic value of combined serum biomarkers for the evaluation of liver fibrosis in chronic hepatitis C infection: A multicenter, noninterventional, observational study. Turk J Gastroenterol 2018; 29: 464-72.